2015
DOI: 10.1109/tps.2015.2426137
|View full text |Cite
|
Sign up to set email alerts
|

Visible Plasma Clouds With an Externally Excited Spherical Porous Cavity Resonator

Abstract: A microwave driven resonator is as an electron/ion cloud generator for illumination and plasma source applications. A sustained porous cavity resonator (PCR) glow discharge is externally excited using a resonant frequency electromagnetic (EM) wave that excites large internal electric fields. The resonator with a Q of 300 amplifies the incident electric field by factors of about 100 causing a breakdown of the neutral gas inside the sphere. The rise time of the fields inside the sphere is Q times the wave period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…One objective of the artificial ionization experiments at HAARP is to form plasma clouds with densities larger than the background ionosphere. In the laboratory, it has been shown that lower powers are needed to sustain a plasma cloud than to initiate the breakdown process [ Bernhardt et al, ]. Some experiments at HAARP have attempted to initiate plasma clouds at a lower gyroharmonic and then hop to the next harmonic frequency (say step from the third to the fourth harmonic) to use the existing plasma cloud as a seed for the denser plasma cloud.…”
Section: Enhanced Densitiesmentioning
confidence: 99%
“…One objective of the artificial ionization experiments at HAARP is to form plasma clouds with densities larger than the background ionosphere. In the laboratory, it has been shown that lower powers are needed to sustain a plasma cloud than to initiate the breakdown process [ Bernhardt et al, ]. Some experiments at HAARP have attempted to initiate plasma clouds at a lower gyroharmonic and then hop to the next harmonic frequency (say step from the third to the fourth harmonic) to use the existing plasma cloud as a seed for the denser plasma cloud.…”
Section: Enhanced Densitiesmentioning
confidence: 99%